Kaizen way to innovation - Abd Razak, Dzulkifli (2010)
It was immensely satisfying to listen to Tun Dr. Mahathir Mohamad speak on a subject as tricky as "technologybased innovation". His onehour encyclopaedic exposé at the Akademi Sains Malaysia International Conference last week took the audience from the mundane issues of innovation to more challenging ones.